Assessment of Babolsar Concrete Pedestrian Bridge Failure for 1964 Flood Event and Retrofitting Practice. (October 2016) - Eslami, Abolfazl; Golafzani, Sara Heidarie; Chenari, Reza Jamshidi
Abstract: The settled (bent) concrete bridge is considered as the oldest pedestrian pass over in Babolsar city of Iran along Caspian Sea shoreline. The Babolrud River bed is formed of soft deltaic deposits because of sedimentation resulting from erosion and general scour from upstream. Consequently there are geotechnical problems such as low bearing capacity, excessive settlement and instabilities. Due to the river flooding in 1964 and local scour around the foundations of the piers, the non-uniform settlement occurred beneath three piers of the middle spans of the bridge. Because of their settlements and rotation of the piers, the decks were locally bent in the support locations. Two different failure analyses were done in order to check the stability of the bridge before, during and after flooding. The results of failure analyses including deterministic method and Monte Carlo simulation, have been compared to each other. Also, a cross correlation coefficient was considered between soil shear strength parameters (i.e. c and φ). The effect of this coefficient and resistance factor was investigated on ultimate bearing capacity, factor of safety and probability of failure. Also, the rehabilitation of the bridge damaged during 1964 flooding is reviewed. The rehabilitation includes: strengthening the sub-construction, balancing and lining up the bridge deck and deck reparations. The monitoring and surveillances after three years of rehabilitation and utilization, have proved the applicability of the practices in rehabilitation of the Babolsar Pedestrian Bridge. Highlights: Babolsar Pedestrian Bridge failed and settled due to flooding event in 1964. Deterministic failure analysis performed for bearing capacity. Reliability analysis shows probability of failure for all loading combinations. Practical steps explained for bridge rehabilitation and retrofitting. Monitoring and surveillance employed for stability and serviceability checks.